Sex differences in the peripheral and central immune responses following lipopolysaccharide treatment in pubertal and adult CD-1 mice. Issue 71 (December 2018) - Sharma, Rupali; Rooke, Jasmine; Kolmogorova, Daria; Melanson, Brett; Mallet, Jean-François; Matar, Chantal; Schwarz, Jaclyn; Ismail, Nafissa
Highlights: Peripheral & central immune responses were examined following LPS treatment. LPS treatment increased plasma cytokine levels and sickness symptoms in all mice. Peripheral cytokines persisted at 8 & 24 h after LPS in adult females. Males expressed greater cytokine mRNA expression in the prefrontal cortex. There are important region- and time-specific differences after LPS treatment. Abstract: Puberty is a critical developmental period that is characterized by significant brain development. Exposure to stress during this time can alter brain functioning setting the stage for long-lasting behavioural outcomes. The objective of this study was to investigate age and sex differences in the peripheral and central immune responses, along with sickness behaviour, following immune stress. The results showed that LPS treatment increased serum cytokine levels and sickness symptoms in all mice. Pubertal males displayed increased IL-1β concentrations at 2 h and increased IL-6 concentrations at 8 h post-treatment whereas increased concentrations of TNFα, IL-10, IL-12, IL-1β, IFNγ, and IL-6 persisted at 8 and 24 h in adult females. Consistent with peripheral cytokines, pubertal males displayed greater IL-1β, TNFα, and IL-6 mRNA expression in the prefrontal cortex at 2 h, whereas adult males expressed more of the aforementioned cytokines at 8 h compared to saline controls. Adult males also displayed greater IL-1β mRNA expression compared to their female counterparts, and adult females displayed greater TNFα mRNA expression compared to their male counterparts. These results not only provide a better understanding of the age and sex differences in acute immune response, but also show important region- and time-specific differences in the response to an immune challenge, and that the peripheral immune response differs from the central response. This highlights the need to examine immune markers in both the periphery and the central nervous system for an accurate depiction of acute immune response following an immune challenge.